2013
DOI: 10.1038/onc.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

CTGF is a therapeutic target for metastatic melanoma

Abstract: Metastatic melanoma remains a devastating disease with a 5-year survival rate of less than five percent. Despite recent advances in targeted therapies for melanoma, only a small percentage of melanoma patients experience durable remissions. Therefore, it is critical to identify new therapies for the treatment of advanced melanoma. Here, we define connective tissue growth factor (CTGF) as a therapeutic target for metastatic melanoma. Clinically, CTGF expression correlates with tumor progression and is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
1
48
0
1
Order By: Relevance
“…Our results showing that fibroblast-derived CCN2 contributes to melanoma metastasis suggest that CCN2 may be a good target for drug intervention in melanoma. Our data are consistent with and extend previous data showing that CCN2 is upregulated in cancer cells in response to hypoxia, oncogenic ras, and YAP/TAZ/hippo and that an antibody against CCN2 blocks progression in animal models of pancreatic cancer and melanoma (Aikawa et al, 2006;Sha and Leask, 2011;Nallet-Staub, 2014;Finger et al, 2014) Periostin, like CCN2, is a matricellular protein upregulated in conditions wherein the ECM is being remodeled (Hamilton, 2008). Our data suggest that periostin operates downstream of CCN2 to promote invasion and is consistent with prior data using periodontal ligament cells that showed rCCN2 induced periostin expression (Asano et al, 2005); however, our data describes to our knowledge a previously unreported link between CCN2 and periostin in tumor metastasis.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showing that fibroblast-derived CCN2 contributes to melanoma metastasis suggest that CCN2 may be a good target for drug intervention in melanoma. Our data are consistent with and extend previous data showing that CCN2 is upregulated in cancer cells in response to hypoxia, oncogenic ras, and YAP/TAZ/hippo and that an antibody against CCN2 blocks progression in animal models of pancreatic cancer and melanoma (Aikawa et al, 2006;Sha and Leask, 2011;Nallet-Staub, 2014;Finger et al, 2014) Periostin, like CCN2, is a matricellular protein upregulated in conditions wherein the ECM is being remodeled (Hamilton, 2008). Our data suggest that periostin operates downstream of CCN2 to promote invasion and is consistent with prior data using periodontal ligament cells that showed rCCN2 induced periostin expression (Asano et al, 2005); however, our data describes to our knowledge a previously unreported link between CCN2 and periostin in tumor metastasis.…”
Section: Discussionsupporting
confidence: 94%
“…14 In recent years, the incidence of melanoma has been increasing rapidly. 15 Melanoma is a cancer that is difficult to cure by conventional therapy, which is one of the reasons why we chose to focus on melanoma in this study. 16, 17, 18 The other reason is that our previous research has shown that CONPs can selectively induce apoptosis and inhibit the proliferation of tumor cells in vitro and that melanoma cells are highly sensitive to CONPs, 19 suggesting that CONPs may be used in the treatment of melanoma.…”
mentioning
confidence: 99%
“…CTGF has previously been implicated as a possible therapeutic target in metastatic melanoma because it is induced by hypoxia and its expression correlates with melanoma patient tumor progression (31). High CTGF expression has also been shown to be important for pancreatic tumor growth (8) and to correlate with poorer survival in glioblastoma, esophageal adenocarcinoma, gastric cancer, and adult acute lymphoblastic leukemia (62,69,102,118).…”
Section: Metastasis-specific Ecm Signaturesmentioning
confidence: 98%